Breeding of the indigenous village fowl - Kasim, Azhar (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
The indigenous village fowl, locally known as ayam kampong asli, is not a breed. They were the descendants from decades of mixed breeding involving imported modern fowl breeds and also the native fowl of Malaysia, the red jungle fowl. With this background, coupled with its scavenging nature, stressful tropical weather, predator threats and lack of attention given to feeding, breeding and feeding, the indigenous village fowl had transformed over the years into a fowl with leaner physique, high agility and flighty in nature. A significant part of this change is influenced by natural breeding, of opportunistic nature with the red jungle fowl as seen by the head appearance and reddish plumage of males in most of the free ranging indigenous breeds of today. However, in certain areas, the predominant nature of the village fowl is of the game type, the result of the movement of game fowls across the border, influenced by interest in keeping game fowls among the locals. Compared to the fast growing white plumage broiler, the meat of the free ranging fowls are regarded a specialty with their firmness and juiciness nature. The shortage of supply of village fowls led to the importation of the slow growing free ranging breeds of colour broiler parent-stocks for the production of commercial hybrids as alternative to the short supply of indigenous village fowl. These colour hybrids can be marketed as early as seven weeks with good nutrition. Indigenous village fowl otherwise are marketed as early at 16th weeks of age. The later maintains its niche market nature with small scale farmers enjoying better price structure.